A large-effect QTL for rice grain yield under upland drought stress on chromosome 1 - Venuprasad, R.; Bool, M.E.; Quiatchon, L.; Sta Cruz, M.T.; Amante, M.; Atlin, G.N. (Springer, 2012)
Drought is a major abiotic stress factor limiting rice production in rainfed areas. In this study we identified a large-effect quantitative trait locus (QTL) associated with grain yield under stress in five different populations on chromosome 1. The effect of this QTL was further confirmed and characterized in five backcross populations in a total of sixteen stress and non-stress trials during 2006 and 2008. In all the stress trials (eight in total) qDTY1.1 showed strong association with grain yield explaining on average 58% of the genetic variation in the trait. Homozygotes for the tolerant parent allele (Apo) yielded on average 27% more than the susceptible parent allele (IR64) homozygotes. Using an Apo/3*IR64 population, the peak of this QTL (qDTY1.1) was mapped to an interval between RM486 and RM472 at 162.8 cM at a LOD score of 9.26. qDTY1.1 was strongly associated with plant height in all the environments; this was probably due to the presence of the sd1 locus in this genomic region. In a Vandana/3*IR64 population segregating for sd1, a strong relation between plant height and yield under stress was observed. The observed relation between increased height and drought tolerance is likely due to tight linkage between qDTY1.1 and sd1 and not due to pleiotrophy of sd1. Thus there is a possibility of combining reduced plant height and drought tolerance in rice. The large and consistent effect of qDTY1.1 across several genetic backgrounds and environments makes it a potential strong candidate for use in molecular breeding of rice for drought tolerance.